An exploratory study of the functional significance of the floral secretory structures in two Miconia species (Melastomataceae) - ANA CARLA FEIO; ANA CATARINA S. FURTADO; ÍTALO ANTÔNIO C. COUTINHO (Anais da Academia Brasileira de Ciências)
Abstract Aiming to verify whether the diversity of secretory structures with their respective exudates are or not responsible for the attendance of floral visitors in Miconia species, the floral secretory structures of two Amazonian species of Miconia were described and interpreted from the functional perspectives and observations of floral visitors. Flowers and floral visitors were collected in the field for 16 months. The flowers were subjected to standard anatomical analyzes using light and scanning electron microscopy, and the secretory structures were evaluated using histochemical tests. The insects were photographed, collected and identified by a specialist. Floral secretory structures (stigmatic papillae and trichomes at the apex of the ovary) were found in M. alata and M. ciliata. Trichomes were found at the hypanthium of M. alata, and of the sepals and receptacles in M. ciliata. In both species, different hydrophilic compounds were detected in the exudates. Only phenolic compounds were found in the trichomes of the M. ciliata receptacle. This study provides information that confirms the hypothesis that other secretory structures and exudates are related to floral visitors, and adds new informations about the features of the secretory structures in Miconia.